ادخلو افی السلم کآفۃ:ارکانِ اسلام اور عصرِ حاضر کے تناظر میں تطبیقی مطالعہUdkhul ū F ī-Il-Silm-i-K āffah: A Practical Study in Context of the Pillars of Islam and Contemporary Perspective (Al-Qamar, 2022)
Islam has given a comprehensive system of worship. The pillars of Islam are the foundations on which the great edifice of Islam is built. “Practical study in the context of the Pillars of Islam and contemporary perspectives” is a topic which deals with the negligence of the Muslims, and it presents the complete pictures of the pillars of Islam.  Prayers are not performed on right time with complete procedure. In the context of Zakat spending the whole year is considered as payment of zakat or by estimation. In the regard of fasting the Muslims has been ordered to perform this important duty through the month avoiding all kind of immorality and certain legitimate matters. The Muslim Ummah is avoiding this by making excuses of various compulsions and diseases. Medical Science has also proved that prayer and fasting can care fatal physical and mental diseases. In the present age the Muslims have adopted Hajj for show off and hypocrisy they are avoiding this important duty by making excuses of so-called compulsions. The purpose of this research is to identify the negligence and faults of contemporary Muslims in performing the pillars of Islam and present the accurate complete picture of them.so that the Muslim Ummah can reform itself.
Keywords: Comprehensive; Foundations; Perspectives; Procedure; Muslim Ummah; Compulsions